Antegrade slow pathway mapping of typical atrioventricular nodal reentrant tachycardia based on direct slow pathway capture. Issue 1 (24th December 2020) - Tobiume, Takeshi; Kato, Ritsushi; Matsuura, Tomomi; Matsumoto, Kazuhisa; Hara, Motoki; Takamori, Nobuyuki; Taketani, Yoshio; Okawa, Keisuke; Ise, Takayuki; Kusunose, Kenya; Yamaguchi, Koji; Yagi, Shusuke; et al.
Abstract: Background: Radiofrequency (RF) ablation of typical atrioventricular nodal reentrant tachycardia (tAVNRT) is performed without revealing out the location of antegrade slow pathway (ASp). In this study, we studied a new electrophysiological method of identifying the site of ASp. Methods: This study included 19 patients. Repeated series of very high‐output single extrastimulations (VhoSESts) were delivered at the anatomical slow pathway region during tAVNRT. Tachycardia cycle length (TCL), coupling interval (CI), and return cycle (RC) were measured and the prematurity of VhoSESts [ΔPM (= TCL – CI)] and the prolongation of RCs [ΔPL (= RC – TCL)] were calculated. Pacing sites were classified into two categories: (i) ASp capture sites [DSPC(+) sites], where two different RCs were shown, and ASp non‐capture sites [DSPC(‐) sites], where only one RC was shown. RF ablation was performed at DSPC(+) sites and/or sites with catheter‐induced mechanical trauma (CIMT) to ASp. Results: DSPC(+) sites were shown in 13 patients (68%). RF ablation was successful in all patients without any degree of atrioventricular block nor recurrence. Total number of RF applications was 1.8 ± 1.1. Minimal distance between successful ablation sites and DSPC(+)/CIMT sites and His bundle (HB) electrogram recording sites was 1.9 ± 0.8 mm and 19.8 ± 6.1 mm, respectively. ΔPL of more than 92.5 ms, ΔPL/TCL of more than 0.286, and ΔPL/ΔPM of more than 1.565 could identify ASp with sensitivity of 100%, 91.1%, and 88.9% and specificity of 92.9%, 97.0%, and 97.6%, respectively. Conclusions: Sites with ASp capture and CIMT were close to successful ablation sites and could be useful indicators of tAVNRT ablation. Abstract : A case of Direct Slow Pathway Capture (DSPC) during typical atrioventricular nodal reentrant tachycardia.